AD, Volume 12, n° 2, 1987 - Full Issue - journal system, (Africa Development, 1987)
CONTENTS African Agriculture: the Next 25 Years Old Problems, Old Solutions and Scientific Foibles Archie Mafeje ....................... 5 The Crisis of the New International Division of Labour, Authoritarianism and the Transition to Free-Market Economies in Africa Eboe Hutchful ....................... 35 Crise Economique et Contre-Pouvoirs au Mali Pascal Baba F. Couloubaly ..................... 57 History and the Question of Technological Development: The Transfer of Technology Revisited Gloria Thomas-Emeagwali ....................... 89 Transfert de Technologie et Perspectives Internationales de Développement en Afrique Sub-Saharienne: Quelques Réflexions Maurice Kamto .............................. 101 The Role of Technology in the Process of Economic Development Ron Matthews ........................... 135 BOOK REVIEWS .......................161 Michael Chege I. Shivji, The State and the Working People in Tanzania I. Mandaza, Zimbabwe: The Political Economy of Transiton Thandika Mkandawire John Sender and Sheila Smith, The Development of Capitalism in Africa (London: Methuen, 1986). PUBLICATIONS RECEIVED ........................171